2009
DOI: 10.1590/s1415-43662009000600004
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos residuais da aplicação de biossólidos e da irrigação com água residuária no crescimento do milho

Abstract: Objetivou-se, com este trabalho, quantificar os efeitos isolados e conjuntos da irrigação com água residuária e de doses de biossólidos no crescimento do milho, após o cultivo da mamona. Conduziu-se um experimento inteiramente casualizado em esquema fatorial [(2 x 3) + 1], com tratamentos englobando dois tipos de água (abastecimento e residuária tratada), três doses de biossólido (0, 75 e 150 kg ha-1) e uma testemunha com fertilizante químico na fórmula NPK, com três repetições, resultando em 21 parcelas. Veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
13

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 3 publications
1
8
0
13
Order By: Relevance
“…In addition, the positive and statistically significant correlation between capitulum growth and grain yield (r = 0.94**) must be pointed out. Plant height results corroborate those obtained by Costa et al (2009), who observed residual effect of sewage sludge on the height of maize plants for the application of 75 and 150 kg ha -1 . On the other hand, these authors did not observe significant increments in stem diameter, despite using sewage sludge doses higher than those tested in this study.…”
Section: Resultssupporting
confidence: 89%
“…In addition, the positive and statistically significant correlation between capitulum growth and grain yield (r = 0.94**) must be pointed out. Plant height results corroborate those obtained by Costa et al (2009), who observed residual effect of sewage sludge on the height of maize plants for the application of 75 and 150 kg ha -1 . On the other hand, these authors did not observe significant increments in stem diameter, despite using sewage sludge doses higher than those tested in this study.…”
Section: Resultssupporting
confidence: 89%
“…The wastewater had in all evaluations higher values when compared to the water supply. Costa et al (2009) confirmed it on studying the stem diameter of the corn stalk. SD was higher for plants receiving wastewater compared to the results of plants that received water supply.…”
Section: Resultsmentioning
confidence: 61%
“…Em plantas de milho, Costa et al (2009) Com relação à variável fitomassa seca de raiz, houve efeito significativo (p<0,01) do fator dose de esterco apenas aos 37 e 44 DAS, não sendo verificado efeito (p>0,01) do fator tipo de água e nem da interação tipo de água x dose de esterco para nenhuma data de estudo. As médias de fitomassa seca da raiz produzida aos 23 e 30 DAS foram de 3,28 e 3,65 g, respectivamente.…”
Section: Resultados E Discussão -Crescimento De Girassolunclassified